Hubungan Pelaksanaan Mabit terhadap Pembiasaan Ibadah Santri di Surau Tahfidzul Qur`an Mushalla Firdaus Tilatang Kamang Agam - Dea Amanda; Jasmienti Jasmienti (Lembaga Yasin AlSys, 2026)
The implementation of Malam Bina Iman dan Taqwa (MABIT) activities as a religious guidance strategy has received attention in various previous studies, but studies that specifically examine its relationship with the habituation of santri worship practices in nonformal educational institutions, such as surau tahfidz, remain limited. This study aims to analyze the relationship between the implementation of MABIT activities and the habituation of santri worship practices at Surau Tahfidzul Qur’an Mushalla Firdaus Tilatang Kamang Agam. This study used a quantitative approach with a correlational design, involving 37 santri selected through the total sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability and were supported by observation, then analyzed using the Pearson Product Moment correlation test and the coefficient of determination. The results showed that there was a significant relationship between the implementation of MABIT and the habituation of santri worship practices, with a correlation coefficient of 0.647, which was in the strong category, and a significance value of 0.00 < 0.05. The implementation of MABIT contributed 41.8% to the habituation of santri worship practices, while 58.2% was influenced by other factors. This finding contributes to the development of habit formation theory in the context of Islamic education while also expanding understanding of the effectiveness of religious guidance programs based on worship practices. The conclusion of this study emphasizes the importance of structured MABIT implementation in shaping santri worship habits and encouraging educational institutions to optimize spiritual guidance programs on a sustainable basis. The implications of this study include a theoretical contribution to enriching the Islamic education literature as well as practical implications for tahfidz institutions in improving the quality of worship guidance, while also opening opportunities for further research on other factors influencing the habituation of santri worship practices.